Implementasi Pembelajaran Berdiferensiasi Berbantuan Program Geogebra Materi Gradien Persamaan Garis Lurus - Agus Prianto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
Straight-line equation gradient learning of VIIID students of SMP Negeri 1 Jepara is very procedural, routine, manual and has not fully met the learning needs of students so that students are less interested, quickly saturated and low student assessment results. Therefore, teachers implement differentiated learning assisted by the Geogebra program. This study used a descriptive method. The purpose of this study describes the implementation of differentiated learning with the Geogebra program, straight line equation gradient material and its results. This research data consists of learning process activities, observations of teacher and student activities, and student assessment results. The implementation of the differentiated learning process is carried out with the following steps (1) presentation of information and learning objectives; (2) the establishment of discussion groups; (3) group discussion and guidance (scaffolding); (4) strengthening and assessment; (5) reflection and feedback. The average results of teacher and student learning process activities were 92.36% and 86.11% with very good criteria. The results of the gradient material assessment obtained an average score of 81.51 (very good category). These results show a positive and significant impact on the learning process and student learning outcomes.